Sulfur Respiration in a Group of Facultatively Anaerobic Natronoarchaea Ubiquitous in Hypersaline Soda Lakes - Sorokin, Dimitry Y.; Messina, Enzo; La Cono, Violetta; Ferrer, Manuel; Ciordia, Sergio; Mena, Maria C.; Toshchakov, Stepan V.; Golyshin, Peter N.; Yakimov, Michail M. (Frontiers in Microbiology, 2018)
The ubiquity of strictly anaerobic sulfur-respiring haloarchaea in hypersaline systems with circumneutral pH has shaken a traditional concept of this group as predominantly aerobic heterotrophs. Here, we demonstrated that this functional group of haloarchaea also has its representatives in hypersaline alkaline lakes. Sediments from various hypersaline soda lakes showed high activity of sulfur reduction only partially inhibited by antibiotics. Eight pure cultures of sulfur-reducing natronoarchaea were isolated from such sediments using formate and butyrate as electron donors and sulfur as an electron acceptor. Unlike strict anaerobic haloarchaea, these novel sulfur-reducing natronoarchaea are facultative anaerobes, whose metabolic capabilities were inferred from cultivation experiments and genomic/proteomic reconstruction. While sharing many physiological traits with strict anaerobic haloarchaea, following metabolic distinctions make these new organisms be successful in both anoxic and aerobic habitats: the recruiting of heme-copper quinol oxidases as terminal electron sink in aerobic respiratory chain and the utilization of formate, hydrogen or short-chain fatty acids as electron donors during anaerobic growth with elemental sulfur. Obtained results significantly advance the emerging concept of halo(natrono)archaea as important players in the anaerobic sulfur and carbon cycling in various salt-saturated habitats.